The Drill Method for Increasing Motivation to Learn FIQH for Middle School Students - Mawaddah, Nurul (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This study discusses the application of the drill method in increasing learning motivation for Jurisprudence for Class VII students. 5 MTs. As'adiyah Puteri II, Sengkang Center, Wajo Regency The main problem studied is the application of the drill method to fiqh subjects and students' learning motivation. This study aims to determine the application of the drill method, how students learn, and how the application of the drill method increases student motivation in MTs. As'adiyah Puteri II, Sengkang Center, Wajo Regency To examine these problems, in this study the authors used descriptive qualitative methods. The approach used is an educational and psychological approach. Through library and field research as well as data collection techniques, the authors conducted observations, interviews, and documentation. The results of the study stated that learning fiqh using the drill-and-kill method can be seen from the way students learn, most of whom are enthusiastic in responding to each piece of the material taught when participating in the learning process. By using the drill-and-kill method, students can easily understand the subject matter presented. To increase students' learning motivation, subject teachers should often give praise or awards so that students are more enthusiastic about participating in the learning process.